(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Child labour remains a persistent challenge in India, despite numerous legal and policy efforts to eradicate it. In Karnataka, child labour takes on unique forms, with children engaged in various sectors, including agriculture, domestic work, manufacturing, and street vending. This article examines the different facets of the child labour problem in Karnataka, with a particular focus on its root causes, the sectors involved, and the socio-economic and cultural dynamics that perpetuate it. By analyzing the legal frameworks, existing policies, and ongoing challenges, this article aims to contribute to the understanding of child labour in the state and offer suggestions for comprehensive solutions.